1995
DOI: 10.1177/000331979504600507
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity and Lipid Profile in Varicose Vein Patients

Abstract: In 20 varicose vein patients, aged twenty-five to forty-five years, and suffering the disease for more than two years, pulse wave velocity (PWV) of the femoral-dorsalis pedis artery of the lower limbs was measured and compared with that of 20 age-matched normal subjects. Blood pressure and fasting serum total cholesterol level, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL) were also estimated for these subjects. PWV showed a significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…There is at least one study which reported abnormal clot lysis time in persons with varicose veins, and speculated about the role of the relative proportions of long-chain versus short-chain fatty acids in the diet [12]. However, a study on the lipid profile among subjects with varicose veins and their controls showed no difference between the two groups [66].…”
Section: Long Hours Of Standing Have Anecdotally Been Associated With Varicose Veins and The Debate Aboutmentioning
confidence: 99%
“…There is at least one study which reported abnormal clot lysis time in persons with varicose veins, and speculated about the role of the relative proportions of long-chain versus short-chain fatty acids in the diet [12]. However, a study on the lipid profile among subjects with varicose veins and their controls showed no difference between the two groups [66].…”
Section: Long Hours Of Standing Have Anecdotally Been Associated With Varicose Veins and The Debate Aboutmentioning
confidence: 99%
“…3-6,16-23 Although multivariate analyses in these studies have shown a strong association between age and PWV, the studies relating PWV to cholesterol and/or dyslipidemia found minimal or inconsistent correlations. [4][5][6]16,17 Furthermore, several studies differ in their conclusions regarding the association between other risk factors and PWV.3,18-23 These inconclusive results may have resulted in part from the fact that most studies were cross-sectional studies. Furthermore, because most individuals have 1 or more cardiovascular risk factors or a cluster of features of the metabolic syndrome (MS) (i.e., obesity, glucose metabolism disturbances, abnormal lipids, and high blood pressure), a clinical condition that seems to be mediated by insulin resistance, 24-27 it may not be appropriate to look only at isolated components.…”
Section: Introductionmentioning
confidence: 99%
“…Weitere allgemeine Einflussfaktoren wie sozialer Status, die Einnahme von oralen Antikontrazeptiva, geringe physische Aktivität, chronische Obstipation, steigende Körpergröße und -gewicht, Arthrose sowie Alkoholkonsum und Rauchen werden teilweise kontrovers diskutiert. Auch Zusammenhänge mit Erkrankungen des arteriellen Gefäßsystems, wie Bluthochdruck und Arteriosklerose werden beschrieben (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Risikofaktorenunclassified